2017
DOI: 10.1080/14686996.2017.1288543
|View full text |Cite|
|
Sign up to set email alerts
|

Role of surface energy and nano-roughness in the removal efficiency of bacterial contamination by nonwoven wipes from frequently touched surfaces

Abstract: Healthcare associated infections (HCAIs) are responsible for substantial patient morbidity, mortality and economic cost. Infection control strategies for reducing rates of transmission include the use of nonwoven wipes to remove pathogenic bacteria from frequently touched surfaces. Wiping is a dynamic process that involves physicochemical mechanisms to detach and transfer bacteria to fibre surfaces within the wipe. The purpose of this study was to determine the extent to which systematic changes in fibre surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 47 publications
(54 reference statements)
2
33
0
Order By: Relevance
“…Therefore the likelihood of either a bacterial "kill" on the contaminated surface or bacterial removal from the contaminated surface is higher with higher surface density. It has previously been shown that bacteria interact with and adhere directly to the fibres in dry wipes (14). Therefore, if more fibres are present at the wipe-contaminated surface interface, there is a greater likelihood of bacterial adhesion and removal.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore the likelihood of either a bacterial "kill" on the contaminated surface or bacterial removal from the contaminated surface is higher with higher surface density. It has previously been shown that bacteria interact with and adhere directly to the fibres in dry wipes (14). Therefore, if more fibres are present at the wipe-contaminated surface interface, there is a greater likelihood of bacterial adhesion and removal.…”
Section: Resultsmentioning
confidence: 99%
“…As reported in these experiments, greater fibre surface area is provided at the interface between the wipe and contaminated surface. As the wipe surface density increases, there will be more surface provided for bacterial adhesion (14).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations